Future Prospects of Artificial Intelligence (AI) in Medical Institute Libraries of Khyber Pakhtunkhwa - Tahira Bibi; Zakria (Indus Journal of Social Sciences, 2025)
This study analyzed the current and potential impact of Artificial Intelligence (AI) technologies in medical institute libraries across Khyber Pakhtunkhwa, Pakistan. Through a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM), the research tested six hypotheses related to cataloging efficiency, user satisfaction, operational automation, technical expertise, and resource challenges. The findings strongly affirm that AI technologies are playing a transformative role in enhancing the functionality and services of medical libraries. From improving the accuracy and efficiency of cataloging processes to enriching the user experience through AI-driven search tools and digital assistants, AI has shown significant promise in reshaping traditional library workflows. However, the study also uncovered notable challenges. The lack of technical expertise among library professionals emerged as a significant barrier to the successful adoption of AI. Additionally, AI technologies were shown to be effective in addressing critical issues such as limited staffing and increasing demands for digital access—common challenges faced by many libraries in developing regions. In conclusion, while AI is not a one-size-fits-all solution, its thoughtful and strategic integration into library systems can lead to substantial improvements in both service delivery and resource management. Medical libraries in Khyber Pakhtunkhwa stand at a pivotal juncture, where embracing AI not only represents technological advancement but also a vital step toward sustainability and responsiveness in an increasingly digital and data-driven world. Policymakers, academic administrators, and library leaders must collaborate to invest in training, infrastructure, and ethical AI implementation to ensure that these technologies are leveraged effectively and inclusively.